Intertextuality: literature and cinema (El Hilo de la Fabula, 2021)
This article is about some uses of intertextuality between cinema and literature. I Walked with a Zombie (1943) is the second of nine films produced by Val Lewton that shaped the horror genre and had a lasting influence on the language of cinema. Reframing the classic Victorian novel Jane Eyre in a Caribbean setting, the film outlines the faultlines of the European colonial enterprise long before the advent of postcolonial studies. Jean Rhys’s partly autobiographical novel Wide Sargasso Sea (1966) rewrites Jane Eyre in a feminist and postcolonial perspective from the point of view of «the madwoman in the attic». In Manuel Puig’s novel Kiss of the Spider Woma, cinema and films, including I Walked with a Zombie, are the intertextual means to the creation of literary character and the figure of a love that has no name.
Keywords: Wal Lewton; Jacques Tourneur; Jean Rhys; Ancho mar de los Sargazos; I Walked with a Zombie; Manuel Puig; El beso de la mujer araña